2020
DOI: 10.1007/s00423-020-01966-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fluorescence angiography: Toward a reliable intraoperative assessment of tissue perfusion - A narrative review

Abstract: Background Accurate intraoperative assessments of tissue perfusion are essential in all forms of surgery. As traditional methods of perfusion assessments are not available during minimally invasive surgery, novel methods are required. Here, fluorescence angiography with indocyanine green has shown promising results. However, to secure objective and reproducible assessments, quantification of the fluorescent signal is essential (Q-ICG). This narrative review aims to provide an overview of the current status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 61 publications
0
42
0
1
Order By: Relevance
“…The authors described the diversity in perfusion parameters and methodology in the field of gastrointestinal surgery, concluding that the application of ICG-NIRF imaging in this field requires standardization before implementation in a clinical setting. A potential means of achieving standardization is by the process of normalization, a mathematical means of correcting for fluctuations in fluorescence intensity, as yet only described in animal studies with promising results [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors described the diversity in perfusion parameters and methodology in the field of gastrointestinal surgery, concluding that the application of ICG-NIRF imaging in this field requires standardization before implementation in a clinical setting. A potential means of achieving standardization is by the process of normalization, a mathematical means of correcting for fluctuations in fluorescence intensity, as yet only described in animal studies with promising results [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced fluorescence imaging with intravenous ICG or fluorescein injection can visualize preserved versus impaired perfusion (e.g., congruent results shown intraoperatively for adrenal perfusion) [9]. However, except for quantitative contrast-enhanced NIR imaging research protocols [74], fluorescent signals and ICG scores are generally assessed subjectively. For ICG injections, the rate at which the fluorescence signal intensity increases, as well as the added signal intensity produced by reinjections, can only be objectively assessed with a quantitative approach, which has not yet been integrated into commercially available NIR imaging systems.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the patient cohort is too small to make further conclusions. Lütken et al evaluated different ways for quantification of FI-ICG and concluded that a combination of timing and inflow intensity reflect clinical outcomes at best [ 34 ]. To date, there is no consensus on the best quantification method for FI-ICG, because it is highly complex, results are conflicting, and no cut-off values have been established yet [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lütken et al evaluated different ways for quantification of FI-ICG and concluded that a combination of timing and inflow intensity reflect clinical outcomes at best [ 34 ]. To date, there is no consensus on the best quantification method for FI-ICG, because it is highly complex, results are conflicting, and no cut-off values have been established yet [ 34 ]. During the last years, our group has clearly demonstrated the impact of using HSI in evaluating the perfusion of the gastric tube during esophagectomy [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 99%